Lying in wait: the resurgence of dengue virus after the Zika epidemic in Brazil - Anderson Fernandes Brito; Lais Ceschini Machado; Rachel J. Oidtman; Márcio Junio Lima Siconelli; Quan Minh Tran; Joseph R. Fauver; Rodrigo Dias de Oliveira Carvalho; Filipe Zimmer Dezordi; Mylena Ribeiro Pereira; Luiza Antunes de Castro-Jorge; Elaine Cristina Manini Minto; Luzia Márcia Romanholi Passos; et al. (Nature Communications, 2021)
Zika and dengue incidence in the Americas declined in 2017–2018, but dengue resurged in 2019 in Brazil. This study uses epidemiological, climatological and genomic data to show that the decline of dengue may be explained by protective immunity from pre-exposure to ZIKV and/or DENV in prior years.